Cytoskeletal form and function in mammalian oocytes and zygotes. (April 2022) - Dunkley, Sam; Scheffler, Kathleen; Mogessie, Binyam
Abstract: The actin and microtubule cytoskeletons of mammalian oocytes and zygotes exist in distinct forms at various subcellular locations. This enables each cytoskeletal system to perform vastly different functions in time and space within the same cell. In recent years, key discovery enabling tools including light-sensitive microscopy assays have helped to illuminate cytoskeletal form and function in female reproductive cell biology. New findings include unexpected participation of F-actin in oocyte chromosome segregation, oocyte specific modes of spindle self-organization as well as existence of nuclear actin polymers whose functions are only starting to emerge. Functional actin-microtubule interactions have also been identified as an important feature that supports mammalian embryo development. Other advances have revealed reproductive age-related changes in chromosome structure and dynamics that predispose mammalian eggs to aneuploidy.